Chemical constituents of Clausena lenis. Issue 21 (2nd November 2021) - Wongthet, Natthawadi; Sanevas, Nuttha; Schinnerl, Johann; Brecker, Lothar; Santimaleeworagun, Wichai; Rosenau, Thomas; Bacher, Markus; Vajrodaya, Srunya
Abstract: Phytochemical examination of Clausena lenis Drake (Rutaceae), collected in Thailand, led to the isolation of seven coumarins, four furoquinolines, two amides, and one flavonoid glycoside. Four of these compounds, one coumarine derivative named as gravelliferone A (3 ), two furoquinoline derivatives (kokusagenin A (8 ) and B (9 )) and one amide, clausenalansamide H (13 ), are reported for the first time. Compound 3 was isolated from the root bark, compound 8 from the stem bark and compounds 9 and 13 from the leaves. The molecular structures of all isolated compounds were established by means of NMR experiments combined with mass spectrometry. Preliminary tests of the lipophilic stem bark extract against various human pathogenic bacteria strains revealed promising effects against Staphylococcus aureus ATCC 43300. Graphical Abstract: